Vowel Space Characteristics of Speech Directed to Children With and Without Hearing Loss. - Wieland, Elizabeth A.; Burnham, Evamarie B.; Kondaurova, Maria; Bergeson, Tonya R.; Dilley, Laura C. (Journal of Speech, Language & Hearing Research, 2015)
Purpose: This study examined vowel characteristics in adult-directed (AD) and infant-directed (ID) speech to children with hearing impairment who received cochlear implants or hearing aids compared with speech to children with normal hearing. Method: Mothers' AD and ID speech to children with cochlear implants (Study 1, n = 20) or hearing aids (Study 2, n = 11) was compared with mothers' speech to controls matched on age and hearing experience. The first and second formants of vowels /i/, /a/, and /u/ were measured, and vowel space area and dispersion were calculated. Results: In both studies, vowel space was modified in ID compared with AD speech to children with and without hearing loss. Study 1 showed larger vowel space area and dispersion in ID compared with AD speech regardless of infant hearing status. The pattern of effects of ID and AD speech on vowel space characteristics in Study 2 was similar to that in Study 1, but depended partly on children's hearing status. Conclusion: Given previously demonstrated associations between expanded vowel space in ID compared with AD speech and enhanced speech perception skills, this research supports a focus on vowel pronunciation in developing intervention strategies for improving speech-language skills in children with hearing impairment.